2010
DOI: 10.1117/1.3514659
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of reporter gene expression using a positron-emission-tomography probe

Abstract: Abstract. Reporter gene/reporter probe technology is one of the most important techniques in molecular imaging. Lately, many reporter gene/reporter probe systems have been coupled to different imaging modalities such as positron emission tomography (PET) and optical imaging (OI). It has been recently found that OI techniques could be used to monitor radioactive tracers in vitro and in living subjects. In this study, we further demonstrate that a reporter gene/nuclear reporter probe system [herpes simplex virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Our group independently performed a systematic validation with both PET and BLI in vivo at multiple time points and found an excellent correlation between OI and PET signals (R 2 5 0.97) (12). Recently, our group also demonstrated that the reporter gene-nuclear reporter probe system (herpes simplex virus type 1 thymidine kinase and 9-(4-18 F-fluoro-3-[hydroxymethyl] butyl) guanine [ 18 F-FHBG]) could be successfully imaged by OI both in vitro and in vivo (13). Statistical analysis showed that both OI and PET displayed good T/N ratios.…”
Section: Cross Validations Of CLI Petmentioning
confidence: 93%
See 2 more Smart Citations
“…Our group independently performed a systematic validation with both PET and BLI in vivo at multiple time points and found an excellent correlation between OI and PET signals (R 2 5 0.97) (12). Recently, our group also demonstrated that the reporter gene-nuclear reporter probe system (herpes simplex virus type 1 thymidine kinase and 9-(4-18 F-fluoro-3-[hydroxymethyl] butyl) guanine [ 18 F-FHBG]) could be successfully imaged by OI both in vitro and in vivo (13). Statistical analysis showed that both OI and PET displayed good T/N ratios.…”
Section: Cross Validations Of CLI Petmentioning
confidence: 93%
“…As is known in nuclear physics, radionuclides decay via a variety of modes including a, b 1 , b 2 , electron capture and isomeric transition. b 1 -emitters include 11 C, 13 N, 15 O, 18 F, 64 Cu, 68 Ga, and 124 I; Robertson et al used 13 N and 18 F to demonstrate CLI (9). On the other hand, 3 H, 14 C, 32 P, 89 Sr, 90 Y, 131 I, and 177 Lu emit principally high-energy b 2 , and the decay of these emitters is often accompanied by g-rays.…”
Section: Recent Advances In Cerenkov Luminescence Imaging (Cli)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such as 18 F-FHBG (9-(4-18 F-fluoro-3-[hydroxymethyl]butyl)guanine) for imaging the reporter geneherpes simplex virus type-1 thymidine kinase (HSV1-tk) [31], and 2-18 F-fluoro-CP-118,954 ( 18 F labeled acetylcholinesterase inhibitor for evaluating the reduction in AChE activity which is very important to the patient with Alzheimer's disease (AD) [32].…”
Section: Of Positron Emission Radionuclidesmentioning
confidence: 99%
“…After passing of the disruption photons are emitted as the displaced electrons return to the ground state. For instance, one Since its emergence, CLI has been investigated for its use in a variety of preclinical applications including in vivo tumor imaging, reporter gene imaging, radiotracer development, multimodality imaging, among others 4,5,9,10,11 . The most important reason why CLI has enjoyed much success so far is that this new technology takes advantage of the low cost and wide availability of OI to image radionuclides, which used to be imaged only by more expensive and less available nuclear imaging modalities such as PET.…”
Section: Introductionmentioning
confidence: 99%